Oracle database 10g Linux administration. - Whalen, Edward, ....- (New York : McGraw-Hill, 2005)
Part I: Oracle on Linux Overview Ch 1. Introduction to Oracle on Linux Ch 2. Linux Architecture Ch 3. Oracle Architecture Part II: Deploying Oracle Database 10g on Linux Ch 4. Sizing Oracle Database 10g on Linux systems Ch 5. Configuring the Linux system for Oracle Ch 6. Installing Oracle on Linux Part III: Oracle RAC on Linux Ch 7. RAC Concepts Ch 8. Deploying RAC on Linux using OCFS Ch 9. Deploying RAC on Linux using RAW Devices Ch 10. RAC on SAN, NAS and Shared SCSI Ch 11. Tuning RAC on Linux Ch 12. Administering Oracle RAC on Linux Part IV: Administering Oracle Database 10g on Linux Ch 13. Administering the Linux System Ch 14. Administering Oracle on Linux Ch 15. Backup Ch 16. Recovery Ch 17. High Availability Options Ch 18. Oracle Standby Database on Linux Ch 19. Oracle Replication on Linux Part V: Oracle Database 10g on Linux Ch 20. Tuning the Oracle Instance on Linux Ch 21. Hardware Tuning and Troubleshooting Ch 22. Tuning SQL Ch 23. Indexes, Partitioning and other Oracle Performance Features
Keywords: Linux (operating system).